Optimal investment and risk control for an insurer with partial information in an anticipating environment. Issue 10 (26th November 2018) - Peng, Xingchun; Chen, Fenge; Wang, Wenyuan
Abstract: This paper considers an optimal investment and risk control problem under the criterion of logarithm utility maximization. The risky asset process and the insurance risk process are described by stochastic differential equations with jumps and anticipating coefficients. The insurer invests in the financial assets and controls the number of policies based on some partial information about the financial market and the insurance claims. The forward integral and Malliavin calculus for Lévy processes are used to obtain a characterization of the optimal strategy. Some special cases are discussed and the closed-form expressions for the optimal strategies are derived.